Is Programme Evaluation the same as Social Impact Measurement? - Tsotsotso, Khotso (Journal of Social Entrepreneurship, 2020)
This study provides an analysis of the practical and theoretical differences in Social Impact Measurements (SIM)–as defined and is core to Impact Investing–and Programme Evaluation (PE) used in Monitoring and Evaluation (M&E). The study is the result of an inspiring effort to converge experiences of both Impact Investment practitioners and investment managers, with those of Programme Evaluators and M&E specialists. A meeting during the AEA’s (American Evaluation Association) ImpaCon conference in Atlanta in 2017. The effort was to facilitate co-learning in order to improve and grow the Impact Investing industry. The study analyses qualitative survey responses from a purposively selected panel of experts including: experienced SIM practitioners and scholars,impact investment managers, programme evaluators and evaluation scholars. Responses are deductively analysed to provide thematic reactions to the research questions. Even though there is a common theoretical intent to determine intervention worth in both SIM and PE, and a common adherence to principles of evaluative thinking; the study concludes that there are clear theoretical and practical differences in participatory and utilisation approach, efficiency and rigour.
Keywords: social impact measurement; Programme evaluation